THE STUDY OF HISTOLOGICAL CHANGES OF CROP IN PEGION DURING BROODNESS - Reshag, Ali Faris (The Iraqi Journal of Veterinary Medicine, 2009)
We noticed that the histological changes in the crop wall was in the lining epithelia only , also wefound that the pigeon milk production in the 12 day of broodness is enough to feed the young , in whichthe thickness of stratified squamous epithelium was 432 micrometer . There was an important staticaldifferent in the weight of crop epithelium thickness in the 12-16 day of incubation in compare with 1 – 6)day of incubation . There were no histological changes in the structure of crop glands.